2019
DOI: 10.1080/15592294.2019.1638700
|View full text |Cite
|
Sign up to set email alerts
|

Global modulation in DNA epigenetics during pro-inflammatory macrophage activation

Abstract: DNA methylation patterns create distinct gene-expression profiles. These patterns are maintained after cell division, thus enabling the differentiation and maintenance of multiple cell types from the same genome sequence. The advantage of this mechanism for transcriptional control is that chemical-encoding allows to rapidly establish new epigenetic patterns 'on-demand' through enzymatic methylation and demethylation of DNA. Here we show that this feature is associated with the fast response of macrophages duri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…It is possible that the body of patients protects itself from the negative epigenetic changes in the long term by acute flares of the disease. A study by Jain et al suggested that white blood cells change their epigenome quickly to better suit the threat they are facing [ 56 ]. However possible, the explanation is purely speculative with current state of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the body of patients protects itself from the negative epigenetic changes in the long term by acute flares of the disease. A study by Jain et al suggested that white blood cells change their epigenome quickly to better suit the threat they are facing [ 56 ]. However possible, the explanation is purely speculative with current state of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The epigenetic level of regulation is critical for the differentiation and functional programming of macrophages [15,113]. There are three levels of epigenetic control of macrophages differentiation and activation: DNA methylation, histone modifications, and microRNA [15,114].…”
Section: Epigenetic Regulation Of Tamsmentioning
confidence: 99%
“…TET2 expression is increased in intratumoral myeloid cells, both in a mouse model of melanoma and in melanoma patients, that is dependent on an IL-1R-MyD88 pathway [135]. Recently, the combination of mass spectrometry and single molecular imaging demonstrated that LPS induces global changes in DNA methylation of the genome of murine macrophages [113,134]. Table 2.…”
Section: Dna Methylationmentioning
confidence: 99%
“…In individuals with asthma, aberrant differentiation of monocytes is observed, notably characterised by a predominance of CD14+/CD16+ cells in blood, typical of tissue macrophages [76,77]. DNA methylation differs between the subsets of monocyte [78], and its localised remodelling is observed during monocyte differentiation into classically activated (M1) and alternatively activated (M2) macrophages [79,80,81]. More specifically, during monocyte to macrophage differentiation, a specific phagocytic gene network is demethylated by TET enzymes [82].…”
Section: Cell-specific Dna Methylation Modifications Associated Wimentioning
confidence: 99%